Reproductive biology of (Anabas testudineus Bloch) living in the swamp area in the Sawah Village, Kampar District, Riau Province. - Nora Oktavia Simanjuntak; Ridwan Manda Putra; Windarti Windarti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Climbing perch (Anabas testudineus) is one of freshwater fish living in the swamp area in the Sawah Village. Information on the biological aspect of this fish, however, is limited. A study aims to understand the reproductive biological aspect of this fish has been conducted from March-April 2018. The fish was sampled once/week for a month period. They were 100 fishes, 36 males and 64 females. Sex ratio of females and males was 1:2.2. In each sampling time there were male fishesin 1st, 2nd, and 3rd while female fishes 1st, 2nd, 3rd and 4th maturity level. The gonado somatic index (GSI) in males were around 0.12-3.33% and females were around 0.68-10.23%.The female’s fecundity were arround 20,193-28,500 eggs/fish, and mature egg diameter ranged from 0.4-0.7 mm.Keywords : Climbing perch, Sex ratio, gonad maturity level, GSI,